Six-month results of intravitreal aflibercept injections for patients with polypoidal choroidal vasculopathy. Issue 8 (23rd February 2015) - Hosokawa, Mio; Shiraga, Fumio; Yamashita, Ayana; Shiragami, Chieko; Ono, Aoi; Shirakata, Yukari; Kimura, Shuhei; Shiode, Yusuke; Kawata, Tetsuhiro; Hosogi, Mika; Fujiwara, Atsushi; Morizane, Yuki
Abstract : Background: This study aims to evaluate the therapeutic effect of intravitreal aflibercept injection for polypoidal choroidal vasculopathy (PCV). Methods: Eighteen eyes of 17 consecutive patients with PCV received three consecutive monthly intravitreal injections of aflibercept and one additional injection 2 months later (four injections totally). All patients underwent eye examinations, which included best-corrected visual acuity (BCVA), fluorescein angiography, indocyanine green angiography, and optical coherence tomography. The primary endpoint of the study was the regression of polypoidal lesions. The secondary endpoints were BCVA, central retinal thickness (CRT) and changes in retinal exudation. Results: Six months after the first aflibercept injection, the polypoidal lesions were completely resolved in 14 eyes (77.7%) and partially resolved in 4 eyes (22.2%). Although branching choroidal vascular networks were still present in all eyes, retinal exudative changes had completely resolved in 17 eyes (94.4%), and the mean CRT decreased significantly from 407.2±100.1 µm to 229.1±57.2 µm (p<0.0001). BCVA (logarithm of the minimal angle of resolution, logMAR) improved significantly from 0.414±0.384 at baseline to 0.297±0.334 after 6 months (p=0.016). Conclusions: At 6 months, aflibercept monotherapy effectively reduced polyps, retinal exudation and CRT in patients with PCV.